Tropical scenery, Port of Spain, Trinidad - Rice, Ben (My University, 2010)
Tropical greenery around the Queen's Park Savannah, Port of Spain. Printed on the right side of the postcard is an advertisement for the Bonanza, a store located in Port of Spain.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Queen's Park Savannah; Savannas; Botanical gardens; Pitch Walk, The